(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
The article examines the experimental evaluation of an ICT-based methodology for developing reading competence among philology students. The study analyzes pre-test and post-test results, percentage growth, Hake gain, and t-test values. The findings show that strategic, level-based, and interactive ICT-supported reading tasks contribute to stronger development of reading competence.